2021
DOI: 10.1186/s12903-021-01578-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temporomandibular disorders among dental students of Saudi Arabia using Diagnostic Criteria for Temporomandibular Disorders (DC/TMD): a cross-sectional study

Abstract: Background Temporomandibular disorders (TMD) are a broad category of conditions arising from the various components of the temporomandibular joint complex. Bio-psychosocial model is the most accepted theory describing the etiopathogenesis of TMD. Dental students are vulnerable to psychological disorders, including anxiety, depression, and stress. Hence, the aim of the current study was to evaluate the prevalence and possible risk factors of TMD among dental students of various academic levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
20
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
(72 reference statements)
7
20
3
2
Order By: Relevance
“…Evidence suggests that TMD is a common complain among students. The prevalence of TMD reported by this study is higher than what has been reported by other studies in Saudi universities which ranged between 25-39%(Alkhudhairy, Al Ramel et al 2018, Srivastava, Shrivastava et al 2021. Studies that addressed general university Saudi students also reported TMD prevalence of 20 to 50% (Zulqarnain,Khan et al 1998, Habib, Al Rifaiy et al 2015, Zwiri and Al-Omiri 2016, Srivastava, Shrivastava et al 2021).…”
contrasting
confidence: 59%
See 3 more Smart Citations
“…Evidence suggests that TMD is a common complain among students. The prevalence of TMD reported by this study is higher than what has been reported by other studies in Saudi universities which ranged between 25-39%(Alkhudhairy, Al Ramel et al 2018, Srivastava, Shrivastava et al 2021. Studies that addressed general university Saudi students also reported TMD prevalence of 20 to 50% (Zulqarnain,Khan et al 1998, Habib, Al Rifaiy et al 2015, Zwiri and Al-Omiri 2016, Srivastava, Shrivastava et al 2021).…”
contrasting
confidence: 59%
“…The prevalence of TMD reported by this study is higher than what has been reported by other studies in Saudi universities which ranged between 25-39%(Alkhudhairy, Al Ramel et al 2018, Srivastava, Shrivastava et al 2021. Studies that addressed general university Saudi students also reported TMD prevalence of 20 to 50% (Zulqarnain,Khan et al 1998, Habib, Al Rifaiy et al 2015, Zwiri and Al-Omiri 2016, Srivastava, Shrivastava et al 2021). All the above-mentioned studies with the exception of Srivastava et al relied on self-administered questioners to identify subjects with TMDs and did not include TMJ clinical examination to confirm the diagnosis as the present study which may explain the difference in prevalence.…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…Degeneration of the TMJ cartilage is among the common features in patients suffering from osteoarthritis, rheumatoid arthritis, and psoriatic arthritis, which then further leads to jaw pain and limited movements that are functionally debilitating [ 18 , 19 , 20 ]. Currently, patients suffering from these pathologies are treated with steroid injections, pulsed electrical stimulation, pharmacological drugs, hyaluronic acid injections, and topical ointments along with stem cell therapy, which provides relief to various degrees to patients, respectively [ 21 , 22 ].…”
Section: Temporomandibular Joint Disordersmentioning
confidence: 99%